Potensi Kayu Untuk Tradisi Pacu Jalur Di Hutan Lindung Sentajo, Kabupaten Kuantan Singingi, Provinsi Riau - Pebriandi, Pebriandi; Darlis, Viny Volcherina; Sribudiani, Evi; Somadona, Sonia; Oktorini, Yosi (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2024)
Forests have various benefits, one of which is social and cultural benefits. Sentajo Protected Forest is used as a source of timber that is used for making lanes in pacu jalur cultural activities. This research is expected to contribute to detailing the timber potential of the Sentajo Protected Forest and formulating recommendations for sustainable management, taking into account ecological, social, and cultural interests, especially about the pacu jalur culture. The method used in this study was to inventory Sentajo Protected Forest stands, especially along the Siriah River, and conduct interviews with local communities. The criteria for trees used for making jalur are trees that have a diameter range of 70 - 100 cm, free branch height of 30 - 40 m, and the tree is not deformed. Trees used for jalur creation are selected trees that are classified as emergent tree species and their growth has slowed down. The results showed that the types of wood used for making Jalur taken from the Sentajo Protection Forest include Meranti Batu (Parashorea aptera), Meranti Sabut (Shorea brachteolata), and Balam Merah (Palaquium burckii).